A rapidly expanding nodule on the lower leg. (1st December 2022) - Butt, Sanaa; Haughey, Veronica; Muncey‐Buckley, Morgan; Evans, Alan; Bryden, Alyson
Abstract: We present a case of a 34‐year‐old man who developed a lesion over his posterior calf. We discuss the clinical and histopathological features, as well as relevant immunohistochemical markers. Click here for the corresponding questions to this CME article.